Modeling social cognitive repercussions of education attainment in Filipino women. [article]. - Obligacion, Freddie R.
Through structural equation modeling, this study demonstrated that high educational attainment results in perceptions of self-efficacy, high self-esteem, a propensity for self-improvement, and achievement-oriented attitudes among 640 Filipino women. Success expectancies, however, were low. Stronger compensatory influences from the respondents high educational attainment, self-efficacy, and achievement-orientation outweighed the depressive impact of low success expectancies on the desire for self-improvement. Findings underscore the importance of continued support for educational programs for the poverty-stricken in developing countries.